Electromagnetic properties of carbon nanotube reinforced concrete composites for frequency selective shielding structures. (30th January 2017) - Micheli, D.; Vricella, A.; Pastore, R.; Delfini, A.; Bueno Morles, R.; Marchetti, M.; Santoni, F.; Bastianelli, L.; Moglie, F.; Mariani Primiani, V.; Corinaldesi, V.; Mazzoli, A.; et al.
Highlights: Carbon nanotube reinforced concretes were characterized in microwave bands. Shielding effectiveness was evaluated by reverberation chamber system. Frequency selective absorber made of reinforced concretes was designed. Particle swarm optimization algorithm was used in the absorber design. Abstract: Carbon nanotube reinforced concrete composites (RCC) were characterized in microwave bands currently employed in wireless telecommunication systems. Dielectric permittivity was retrieved by waveguide method and adopted to compute shielding effectiveness of RCC structures having different thickness/filler content. The shielding was also evaluated by reverberation chamber set up; theoretical calculations and measured values are in close agreement, thus testifying to the procedure reliability. Finally, a frequency selective absorber made of RCC layers was designed with the aid of a numerical optimization tool (particle swarm algorithm); the discussion of results is supported by a finite element method analysis of the layered structure.